Conservative Management of Morbidly Adherent Placenta: Expert Review. Issue 4 (December 2016) - Fox, K.A.; Shamshirsaz, A.A.; Carusi, D.; Secord, A.A.; Lee, P.; Turan, O.M.; Huls, C.; Abuhamad, A.; Simhan, H.; Barton, J.; Wright, J.; Silver, R.; et al.
Abstract : ( Am J Obstet Gynecol 2015;213(6):755–760) Morbidly adherent placenta (MAP) includes the spectrum of placenta accreta, increta, and percreta and is a cause of major morbidity and mortality in pregnant women. In the last century, the incidence of MAP has risen from approximately 1 in 20, 000 live births in 1928 to 1 in 533 in 2002.